Literatur Review: Pembatasan energi untuk peningkatan umur panjang. Manajemen alternatif terhadap metabolik obesitas - Sophia Rose; Etika Ratna Noer; Muflihatul Muniroh; Apoina Kartini (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Diet development today tends to lead to accelerated growth of chronic diseases. Obesity plays a negative role in the development of chronic disease. This risk factor also occurs in the aging process. The condition of organ tissue dysfunction and cell death that occurs with aging also occurs in obesity due to chronic inflammation. This study analyzes the beneficial effects of applying Calorie Restriction (CR) or Energy Restriction (PE) to achieve a long life span, especially in obese individuals. This article is a literature review study with qualitative analysis by searching the PubMed electronic database from February to July 2021 and searching for articles through Meta-analysis, Review, and Systematic Review. Six articles have high relevance. References obtained were compiled and reviewed by summarizing and analyzed by triangulation. Furthermore, examining previous research's pros and cons finally gives alternative solutions. The results of the study showed the application of the PE method by reducing daily energy consumption without causing the risk of malnutrition because it still considers an essential nutrient. In conclusion, the benefits of PE have an impact on slowing down aging molecularly. Slowing down the aging process can increase a person's life expectancy.